Narrative of Love and Tolerance on Social Media - Ibad, M. Nashoihul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study explores public reception of the Tepuk Sakinah campaign initiated by Indonesia’s Ministry of Religious Affairs (Kemenag) as a digital da’wah effort to promote love, family harmony, and religious tolerance through the TikTok platform. Drawing on the phenomenon of local wisdom entering global digital communication, this research employs a qualitative approach using netnography combined with content analysis of user comments. Data were collected from all Tepuk Sakinah videos uploaded by Kemenag’s official account and participating users during the active campaign period, including public comments and engagement metrics. The findings reveal that narratives of love and tolerance were predominantly received positively, indicated by supportive comments, expressions of pride in local culture, and encouragement to share the content. Nevertheless, critical remarks also emerged, questioning the authenticity of digital da’wah practices and highlighting differences in religious interpretation. These results demonstrate that social media functions not only as a channel for disseminating Islamic messages but also as a site of meaning negotiation, where local wisdom can bridge Islamic moderation and global harmony. The study contributes to the development of government communication strategies for utilizing digital platforms to strengthen messages of tolerance within the dynamic online public sphere.